Influence of baffles in heat transfer fluid characteristics using CFD evaluation. Issue 1 (31st December 2022) - Mukilarasan, Nedunchezhiyan; Karthikeyan, R.; Ramalingam, Sathiyamoorthi; Dillikannan, Damodharan; Ravikumar, J.; Sampath, Senthil; Kaliyaperumal, Gopal
Abstract : This research focuses on the fluid flow and heat transfer characteristics of shell side flow in shell and tube heat exchangers. A CFD analysis is employed to investigate the shell sidestream, and a numerical simulation is being validated. The baffles' configurations of shell and tube heat exchanger are modified improve the heat transfer characteristics. The orientations of alternate baffles were varied with various angles and named cases 1–5. Out of six baffles, the odd number baffles (1, 3, 5) from the inlet side are at a constant position (0°:0°:0° inclination) in all the cases, whereas the baffles (2, 4, 6) are altered with various angular orientations (0°:0°:0°; 45°:45°:45°; 45°:−45°:45°; 90°:90°:90°; 90°:−90°:90° inclination). The velocity is not increased in 45° baffle configuration compared to other cases, but the heat transfer coefficient is improved. So, a 45°:±45°:45° baffle configuration is proposed that produces better performance without altering the heat exchanger designs.